ASPERGILLUS NIGER AS THE RAPID PRESS MUD COMPOSTING AGENT - U. Naeem; M. A. Qazi; I. u. Haq; M. Afzaal (Journal of Animal and Plant Sciences, 2022)
Composting with efficient microbes is considered a sustainable strategy for effective conversion of agricultural discards into a productive biofertilizer. The present study was designed to isolate fungal strain efficient in releasing hydrolytic enzymes for accelerated decomposition and value addition of press mud (PM). In order to tolerate higher temperatures and pH variations during composting, the analysis specifies the different enzymatic behavior at varied temperature and pH range and the strain was also tested for aflatoxins production to produce biofertilizer safe for crop application. The physicochemical characteristics of PM such as total organic carbon (TOC), C/N ratio, electrical conductivity (EC), cation exchange capacity (CEC), total Kjeldahl nitrogen (TKN), total phosphorus (TP), and total potassium (TK) during composting were also studied as compared to control. The results indicated that among seven fungal isolates, Aspergillus niger (A. niger) PM-4 was selected as the best enzyme producers by producing carboxymethyl cellulase (CMCase) α-Amylase, pectinase, and xylanase at a broader temperature and pH spectrum. Composting of PM with A. niger PM-4 leads to significant reduction in TOC (21.2%), C/N ratio (21.3%), increase in EC (25%), CEC (98%), TKN (10.5%), TP (9.2%), and TK (41%) compared to control with one month maturity duration. The A. niger PM-4 also inhibiting mycotoxin growth (aflatoxins) and its inoculation into PM generated mature biofertilizer with germination index (GI) 96.5% after a month representing a cheaper, effective and sustainable approach for waste utilization.
Keywords: Biofertilizer; Bio-inoculant; Aspergillus niger; Composting; Hydrolytic enzymes